2021
DOI: 10.1007/s11130-021-00910-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Nixtamalization Extrusion Process and Tortillas Making on the Stability of Anthocyanins from Blue Corn through the Kinetic and Thermodynamic Parameters

Abstract: The blue corn-based products are considered functional foods due to their high concentration of anthocyanins. The aim of this study was to estimate the kinetic and thermodynamic parameters of the thermal degradation of anthocyanins from extruded nixtamalized corn products. A comparative study of anthocyanins thermal stability in these matrices in a buffer solution (pH 2.5) was investigated at different temperatures (60, 75 or 90 °C). Results showed the mechanism of anthocyanins degradation followed first-order… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…The degradation of anthocyanins in blue corn-based extruded nixtamalized products followed a first-order model at temperatures ranging from 60 • C to 90 • C at pH 2.5, with the determined thermodynamic parameters showing that the process was endothermic and non-spontaneous [79]. The authors of the paper showed that anthocyanin degradation kinetics of extruded corn flour and of prepared tortilla were similar, although tortilla making involved much higher temperatures (300 • C) than those applied in the extrusion process, probably in relation to the matrix protective effects, which caused a slower heat flow to the center of the tortilla due to some anatomical parts of the kernel.…”
Section: Behavior Of Anthocyanins During Processing Involving Thermal Treatment Of Food Rich or Enriched With Anthocyaninsmentioning
confidence: 99%
“…The degradation of anthocyanins in blue corn-based extruded nixtamalized products followed a first-order model at temperatures ranging from 60 • C to 90 • C at pH 2.5, with the determined thermodynamic parameters showing that the process was endothermic and non-spontaneous [79]. The authors of the paper showed that anthocyanin degradation kinetics of extruded corn flour and of prepared tortilla were similar, although tortilla making involved much higher temperatures (300 • C) than those applied in the extrusion process, probably in relation to the matrix protective effects, which caused a slower heat flow to the center of the tortilla due to some anatomical parts of the kernel.…”
Section: Behavior Of Anthocyanins During Processing Involving Thermal Treatment Of Food Rich or Enriched With Anthocyaninsmentioning
confidence: 99%